Anarchism and Political Modernity - Jun, Nathan (Contemporary Anarchist Studies, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Anarchism and Political Modernity looks at the place of 'classical anarchism' in the postmodern political discourse, claiming that anarchism presents a vision of political postmodernity. The book seeks to foster a better understanding of why and how anarchism is growing in the present. To do so, it first looks at its origins and history, offering a different view from the two traditions that characterize modern political theory: socialism and liberalism. Such an examination leads to a better understanding of how anarchism connects with newer political trends and why it is a powerful force in contemporary social and political movements. This new volume in the Contemporary Anarchist Studies series offers a novel philosophical engagement with anarchism and contests a number of positions established in postanarchist theory. Its new approach makes a valuable contribution to an established debate about anarchism and political theory. It offers a new perspective on the emerging area of anarchist studies that will be of interest to students and theorists in political theory and anarchist studies.